Hubungan Metode Jarimatika dengan Perkalian dalam Pembelajaran Matematika pada Siswa Sekolah Dasar - Intan Pritama Putri; Ramanata Disurya; Farizal Imansyah (Departement of Mathematics Education, 2024)
Mathematics is a subject that is very less popular in school learning, therefore the problem faced in this research is the lack of ability to calculate multiplication. The aim of this research is for students to improve their ability to calculate multiplication. This research uses correlational research with a quantitative method approach, Quantitative correlational research is research that is intended to determine whether there is a relationship between two or more variables. Researchers use data collection techniques through observation, interviews, documentation. then technical data analysis is used through hypothesis testing, normality testing, coefficient of determination testing, and homogeneity testing. Based on the results of research hypothesis testing that has been carried out, a value of 0.864 > 0.468 is obtained, indicating that there is a fairly close relationship between the Jarimatics method and multiplication. And by obtaining a significant value of 0.000 where 0.000 < 0.005, we can conclude that Ho is rejected and Ha is accepted.